Mirodenafil improves cognitive function by reducing microglial activation and blood–brain barrier permeability in ApoE4 KI mice - Park, Yejin; Moon, Subin; Jung, Harry; Park, Songyi; Kim, Ju Won; Song, Dan-Gyeong; In, Yong-Ho; Han, Sang Won; Sohn, Jong-Hee; Lee, Chan Hee (Frontiers in Aging Neuroscience, 2025)
IntroductionAlzheimer’s disease (AD) has significant public health concerns in the aging society. AD can compromise brain function and lead to severe neurological abnormalities associated with dementia. The human Apolipoprotein E (ApoE4) gene is a strong risk factor for AD. However, comprehensive analyses and improvements of mouse models expressing ApoE4 remain largely unexplored.MethodsApoE4 knock-in (KI) mice were used to investigate the role of humanized ApoE4 in hippocampal histological changes and cognitive impairment. Cerebrovascular perfusion, blood–brain barrier (BBB) integrity, microgliosis, and amyloid-beta 42 (Aβ42) accumulation were examined. Cognitive functions were assessed using the Morris water maze, Y-maze, and novel object recognition tests. Mirodenafil, a potent and selective phosphodiesterase 5 inhibitor (PDE5i), was orally administered to ApoE4 KI mice for 4 weeks. An in vitro BBB model and BV2 microglial cells were used to investigate endothelial permeability and inflammation.ResultsApoE4 KI mice exhibited not only reduced cerebrovascular perfusion and CLN-5 expression but also increased microgliosis and Aβ42 accumulation in the hippocampus. These phenomena were accompanied by impaired cognitive functions. Mirodenafil administration reversed the histological and behavioral alterations induced by ApoE4 KI. In vitro, mirodenafil treatment mitigated Aβ42-induced endothelial permeability and lipopolysaccharide-induced microglial inflammation.DiscussionThese findings suggest that mirodenafil enhances cerebrovascular function, preserves BBB integrity, and mitigates neuroinflammation in ApoE4 KI mice, leading to cognitive improvement. PDE5 inhibition may serve as a promising therapeutic approach for addressing ApoE4-associated cerebrovascular and cognitive dysfunction.